Case studies of photospheric magnetic field properties of active regions associated with X-class solar flares - Teh, Wai-Leong; Farahana Kamarudin (Penerbit Universiti Kebangsaan Malaysia, 2021)
Solar flares are a transient phenomenon occurred in the active region (AR) on the Sun’s surface, producing intense emissions in EUV and soft X-ray that can wreak havoc in the near-Earth space mission and satellite as well as radio-based communication and navigation. The ARs are accompanied with strong magnetic fields and manifested as dark spots on the photosphere. To understand the photospheric magnetic field properties of the ARs that produce intense flares, two ARs associated with X-class flares, namely AR 12192 and AR 12297, occurred respectively on 25 October 2014 and 11 March 2015, are studied in terms of magnetic classification and various physical magnetic parameters. Solar images from the Langkawi National Observatory (LNO) and physical magnetic parameters from the Space-weather HMI Active Region Patches (SHARP) are used in this study. A total of seven SHARP magnetic parameters are examined which are calculated as sums of various magnetic quantities and have been identified as useful predictors for flare forecast. These two ARs are classified as βγδ sunspots whereas their formation and size are quite different from each other. Our results showed that the intensity of a flare has little relationship with the area of an AR and the magnetic free energy; and the temporal variation of individual magnetic parameter has no obvious and consistent pre-flare feature. It is concluded that the temporal variation of individual magnetic parameter may not be useful for predicting the onset time of a flare.